Herding pattern among Bronze Age steppe communities: An ethnographic approach to mapping pasture in the Southeastern Ural Mountains, Russia - Ng, Chuenyan; Wei, Weiyan; Yu, Chong; Zheng, Junlei (Frontiers in Ecology and Evolution, 2022)
Recent ethnographic data can assist with the examination of Bronze Age pastoralist herding patterns. However, there are still missing links between the archaeological record and available ethnographic data from the Southeastern Ural Mountains regions. One way to explore the answer to this question is to use archaeobotanical data to understand the herding pattern in prehistory, which in many ways act as a bridge between pastoralist subsistence economy and plant exploitation strategy in the microenvironment. Compared with previous research, this ethnographic study was undertaken through field research based on the analysis results of the archaeobotanical record recovered from the Bronze Age Stepnoye settlement. The archaeobotanical sampling associated with the excavation of the Stepnoye settlement indicated a significant pattern of local wild resource exploitation for humans and livestock. Therefore, regional ethnographic study and pasture mapping in local catchment zone provide essential comparative data to interpret the herding-related plant remains and further discussion of herding patterns among Bronze Age pastoralist communities in this area.